2017
DOI: 10.1186/s41043-016-0077-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing contraceptive use and non-use among women of advanced reproductive age in Nigeria

Abstract: BackgroundFactors influencing contraceptive use and non-use among women of advanced reproductive age have been insufficiently researched in Nigeria. This study examines factors influencing contraceptive use and non-use among women of advanced reproductive age in Nigeria.MethodsSecondary data were pooled and extracted from 2008 and 2013 Nigeria Demographic and Health Surveys (NDHS). The weighted sample size was 14,450 women of advanced reproductive age. The dependent variable was current contraceptive use. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
90
3
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(129 citation statements)
references
References 26 publications
32
90
3
4
Order By: Relevance
“…This is in contrast to the pool of evidence established by previous studies that found a positive association between level of education attained by women and prevalence of contraceptives [13,[22][23][24][25]. This anomaly can be attributed to the low population of women with tertiary education in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in contrast to the pool of evidence established by previous studies that found a positive association between level of education attained by women and prevalence of contraceptives [13,[22][23][24][25]. This anomaly can be attributed to the low population of women with tertiary education in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…This will help in reducing the risk of mother-to-child transmission. Also, knowledge of long acting methods was reported to be significantly associated with utilization26 and women’s knowledge of contraceptive was a significant predictor of their contraceptive practice 27. All these are indications for improving knowledge of WLHIV on contraceptive options available to them.…”
Section: Discussionmentioning
confidence: 96%
“…Finally, there was a significant difference in the proportion of individuals who reported using contraceptives when comparing those who were aware of their HIV status (62.7%; 95% CI: 57.3-67. 7) and those who had never tested for HIV (51.6%; 95% CI: 44.7-58.4; p = 0.007). Figure 1 below shows that 1% of women reported that they were sterilized, 1% of females reported that their partner was sterilized, 9.6% of females reported that they were on the pill, 2.3% reported that they had an intrauterine device, 34.8% reported that they were using injectables, 3.3% reported that they were using the rhythm method, 6.3% reported that they were using the withdrawal method, 1% reported that they used the emergency contraception, and 40.6% reported using condoms.…”
Section: Discussionmentioning
confidence: 98%
“…There are several factors predicting none or low usage of contraceptives amongst women. Research evidence has shown that some socio-demographic and behavioral factors influence contraceptive use [6][7][8]. For example, low contraceptive use has been associated with sociodemographic factors such as women coming from rural areas, those with low educational qualification, low socio-economic status, limited knowledge on accessibility, and awareness of contraceptives [9].…”
Section: Introductionmentioning
confidence: 99%